Drug Delivery System in Feline - Herdiana, Yedi; Wilar, Gofarana; Sofian, Ferry Ferdiansyah; Pitaloka, Annisa Dyah; Nurhijriah, Yasinta; Safira, Rayhan Zarra; Salsabila, Annisa Siti; Z, Maziyatunisa (Indonesian Journal of Pharmaceutics, 2022)
The drug delivery system is an attractive field of study since it has several applications in veterinary and human medicine. In the realm of veterinary medicine, the discovery of new routes of administration or new delivery systems to regulate the release of medications is of great importance. Due to the high number of animals and the special issues related to the administration of drugs and their market potential is very large, it is necessary to modify the dosage form to produce an effective and practicable preparation. Cats are the most popular pet in the world, outnumbering dogs by a ratio of three to one. It is vital to understand the prevalent illness patterns and limits of traditional delivery systems to establish appropriate dosage forms for cats. We believe this publication will be of interest to veterinarians and pharmaceutical scientists working in the field.